Poverty, malaria and health system reforms in Africa : three studies applied in Cameroon - (:unkn) unknown (My University, 2018)
This thesis deals with poverty, malaria and health system reforms in Africa. It is motivated by persistently high levels of social inequality, prevalence and mortality related to malaria in sub-Saharan Africa in a context characterized by widespread use of insecticide-treated mosquito nets (ITNs) and the implementation of innovative reforms in health system. We focused on three cases studies applied to Cameroon. Since 2012, the country has been experimenting the Performance Based Financing (PBF) approach in its health system. We used data from the PBF impact assessment surveys conducted in this country in 2012 and 2015.Our results show first that the households’ low level of standard of living predisposes its members under 5 to malaria. Secondly, we find that the malaria shocks, very frequent for children under 5 years, affect negatively the mothers. Thirdly labor supply. We find that the reforms introduced by PBF have a significant and positive impact on the therapeutic use in case of malaria of children under 5 in Cameroon, especially among the poor children and in rural areas.The results obtained could guide endemic sub-Saharan countries in the implementation of the new roadmap for the achievement of sustainable development goals, formulate consistent policies against malaria and against poverty.
Keywords: African Research